2006
DOI: 10.1088/1367-2630/8/2/020
|View full text |Cite
|
Sign up to set email alerts
|

The healing mechanism for excited molecules near metallic surfaces

Abstract: Radiation damage prevents the ability to obtain images from individual molecules. We suggest that this problem can be avoided for organic molecules by placing them in close proximity with a metallic surface. The molecules will then quickly dissipate any electronic excitation via their coupling to the metal surface. They may therefore be observed for a number of elastic scattering events that is sufficient to determine their structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…An explanation could be that the ring of the porphyrin molecule, in proximity to the metallic substrate, strongly stabilizes the entire molecule, making it less sensitive to radiation damage. 19 However, we could not detect any edge jump in the energy range of the Cl-L 2,3 edges. Density functional theory ͑DFT͒ calculations 18 showed that the ferromagnetic coupling for the molecules to the substrate occurs only when the Cl atom is detached.…”
Section: Methodsmentioning
confidence: 56%
“…An explanation could be that the ring of the porphyrin molecule, in proximity to the metallic substrate, strongly stabilizes the entire molecule, making it less sensitive to radiation damage. 19 However, we could not detect any edge jump in the energy range of the Cl-L 2,3 edges. Density functional theory ͑DFT͒ calculations 18 showed that the ferromagnetic coupling for the molecules to the substrate occurs only when the Cl atom is detached.…”
Section: Methodsmentioning
confidence: 56%
“…The HE-XRD setup at this beamline is described in more detail elsewhere [39]. Although radiation damage to individual nanoparticles should be reduced as much as possible, nanoparticles on a metallic substrate can be healed through a healing mechanism that involves a neutralization process [40].…”
Section: Methodsmentioning
confidence: 99%
“…As illustrated in Figure 4, the positron transitions from a scattering state to a metal surface state and the excess of energy is transferred to a valence electron emitted in the vacuum. Such non-radiative decay phenomenon is of great scientific interest in different areas of physics and chemistry [36][37][38]. For instance, new designs for solar energy conversion use non-radiative mechanisms for the energy transfer from excitons created on a photon absorption layer to high mobility charge carriers inside the solar cell.…”
Section: Hybrid Plasmonic-sqd Platformmentioning
confidence: 99%